The naturalism approach to language - Ali Abdul Kazim Hamid / Dhameer Hussain ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Western linguistic thought is considered one of the greatest scientific products in the era of the emergence and development of science at all levels. It has opened many horizons of a scientific nature due to its connection with other sciences. The study of language is no longer limited to the known linguistic levels, as the study of language has become a natural approach, as is the case in other natural sciences. Therefore, we find linguistics titles with a scientific dimension, such as (biological, forensic, mathematical, and computer linguistics, ( and our study is an attempt to uncover that approach called naturalism. Because of its influence on natural scientific approaches, such as the positivist and experimental approach, which is a basic feature for understanding the natural sciences, linguistics, especially structural and generative studies, benefit from that approach so that the scientific character is present in their linguistic studies. This enhances the comprehensiveness of linguistic studies for scientific approaches and for them to be on par with those. Natural Sciences.